Deep ocean 14C ventilation age reconstructions from the Arctic Mediterranean reassessed - Ezat, Mohamed; Rasmussen, Tine Lander; Skinner, Luke C.; Zamelczyk, Katarzyna (Earth and Planetary Science Letters, 2019)
Source at https://doi.org/10.1016/j.epsl.2019.04.027. The present-day ocean ventilation in the Arctic Mediterranean (Nordic Seas and Arctic Ocean), via transformation of northward inflowing warm Atlantic surface water into cold deep water, affects regional climate, atmospheric circulation and carbon storage in the deep ocean. Here we study the glacial evolution of the Arctic Mediterranean circulation and its influence on glacial climate using radiocarbon reservoir-age reconstructions on deep-sea cores from the Fram Strait that cover the late glacial period (33,000–20,000 yr ago; 33–20 ka). Our results show high Benthic-Planktic 14 C age differences of ∼1500 14 C years 33–26.5 ka suggesting significant water column stratification between ∼100–2600 m water depth, and reduction and/or shoaling of deep-water formation. This phase was followed by breakup of the stratification during the Last Glacial Maximum (LGM; 26–20 ka), with Benthic-Planktic 14 C age differences of ∼250 14 C years, likely due to enhanced upwelling. These ocean circulation changes potentially contributed to the final intensification phase of glaciation via positive cryosphere-atmosphereocean circulation-carbon cycle feedbacks. Our data also do not support ‘extreme aging’ of >6000 14 C years in the deep Arctic Mediterranean, and appear to rule out the proposed outflow of very old Arctic Ocean water to the Nordic Seas during the LGM and to the subpolar North Atlantic Ocean during the deglacial period.